Plasma fibrinogen — a major coronary risk factor - Stone, M.C. (1985)
The role of plasma fibrinogen as a potential indicator of susceptibility to heart attacks was studied in a sample of 297 men aged 40-69 years at entry who were initially free from overt coronary heart disease. During a mean observation period of 7.3 years (range 0.1-16.1) new heart attacks occurred in 40 men. There was a significant positive correlation between initial plasma fibrinogen levels and the subsequent incidence of heart attacks. In men with high cholesterol or high systolic blood pressure levels the incidence of heart attacks was respectively six times and 12 times greater in those with high plasma fibrinogen levels than in those with low fibrinogen levels. In multivariate models plasma fibrinogen was a highly significant and independent explanatory variable, at least as important as serum cholesterol, blood pressure or cigarette smoking. These results suggest that high plasma fibrinogen levels are an important coronary risk factor and should be included in profiles used to identify those at high risk of heart attacks.